2022
DOI: 10.1155/2022/9593843
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Determination by a Single 1535 nm Pulsed Photoacoustic Technique: A Multiple Calibration for the External Factors

Abstract: Photoacoustic spectroscopy has been proved to be a potential method for noninvasive blood glucose detection. We used 1535 nm pulsed laser to excite photoacoustic signal in glucose solution and then explored the influence of different glucose concentration on photoacoustic signal to analyze the sensitivity of photoacoustic signal to glucose at this wavelength. We designed a simple photoacoustic cell structure, which used a focused ultrasonic transducer to receive signals, so as to reduce signal attenuation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…(ii) PAS glucose detection instrument and process. Reprinted with permission from ref . Copyright 2022 HINDAWI Ltd.…”
Section: Noninvasive Detection Methods Of Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…(ii) PAS glucose detection instrument and process. Reprinted with permission from ref . Copyright 2022 HINDAWI Ltd.…”
Section: Noninvasive Detection Methods Of Glucosementioning
confidence: 99%
“…After the light source of a specific wavelength hits the sample, the measured medium in the sample is heated and expanded to generate ultrasonic waves (Figure 5i). 118 There are two categories of excitation forms for light sources, pulsed laser (Figure 5ii) 119 and continuous wave. Strong PA signals can be produced by pulsed photoacoustic spectrum, but the requirements of the pulsed light source are strict.…”
Section: Detection Of Glucosementioning
confidence: 99%
“…Besides, their results showed that in vivo spectroscopic glucose monitoring is sensitive to the skin condition with significant inhomogeneities and the probing area. Yang [ 15 ] utilized 1535 nm pulsed laser to excite photoacoustic signal in glucose solution and explored the influence of different glucose concentration on photoacoustic signal. At the same time, the external factors affecting the photoacoustic signal, such as laser energy, liquid temperature and detection distance were explored, and a calibration method was also proposed.…”
Section: Introductionmentioning
confidence: 99%